Does Structural Empowerment of Nurse Leaders Moderate the Relationship Between Destructive Leadership and Nursing Outcomes?—A Cross‐Sectional Study - Nurmeksela Anu; Hult Marja; Häggman‐Laitila Arja; Terkamo‐Moisio Anja (Wiley, 2025)
Aim: To describe how nursing staff assess their superiors' destructive leadership and nurse leaders' structural empowerment. A further aim is to examine the associations between destructive leadership and staff outcomes and how nurse leaders' structural empowerment moderates these associations.
Design: A cross-sectional study.
Methods: The data were collected during November 2022-April 2023. Nursing staff assessed their work well-being, commitment, decision-making and career advancement. Destructive leadership was evaluated using the Employment Precariousness Scale and some additional questions. Nurse leaders' structural empowerment was assessed using the Conditions For Work Effectiveness Questionnaire-II. The data were analysed using statistical methods including linear regression.
Results: Nursing staff (n = 381) assessed destructive leadership as rare, but it negatively associated with their commitment, decision-making, career advancement and work well-being. Nurse leaders' (n = 97) structural empowerment had a positive association with nursing staff outcomes. The interaction between destructive leadership and nurse leaders' structural empowerment positively affected the work well-being and commitment of nursing staff. The models explained 32% of nurses' work well-being and 19% of their commitment.
Conclusion: Destructive leadership undermines nursing staff outcomes. Structural empowerment of nurse leaders should be enhanced to protect against destructive leadership and other protective factors should be explored in the future to identify and prevent destructive leadership.
Implications for the profession: Organisations should provide nurse leaders with appropriate resources and support to enhance their empowerment and opportunities to improve their leadership skills and expertise and should develop ways of identifying destructive leadership patterns and policies to resolve situations in which destructive leadership occurs.
Impact: A work environment that empowers nurse leaders may reduce the effect of destructive leadership on staff well-being, commitment, decision-making and career advancement. The significance of protective factors against destructive leadership should be explored using more robust methods in future research.
Reporting method: A STROBE checklist.
Patient or public contribution: None.